The potential mRNA target sites for the ribosomal protein L10 found in Streptomyces griseus and S. coelicolor give evidence for the autogenous regulation of expression of the rplJL genes - Paton, E.B. (Биополимеры и клетка, 1995)
On the basis of structural similarity between the m- and rRNA binding sites which underlies the molecular mechanism of the autogenous control of expression of the rplJL genes, mediated in prokaryotic organisms by ribosomal protein L10, we attempted to find the potential mRNA target sites in S. griseus and S. coelicolor. The potential targets found in both species of Streptomyces are of highly conserved structure and contain elements similar with the L10 binding domain of the 23S RNA. Compared to the L10, mRNA targets of Enterobacteria, Thermotoga maritima and Synechocystis, the target sites of Streptomyces contain a larger number of conserved and specific structural elements, similar in both analyzed species. Comparison of the structural organization of the "Streptomyces" and "Enterobacterial" types of the L10 mRNA targets with the structure of the L10 binding domain in the 23S RNA reveals that the elements, conserved in all the mentioned targets, are located in the ssA and dsA regions. The structure of the potential L10 mRNA target sites, which mimic the rRNA target of the regulatory ribosomal protein L10, gives evidence for the autogenous L1-0mediated control of expression of the rplJL genes in Streptomyces. Описано структурові особливості виявленого у представників Streptomyces постійного сайта зв'язування рибосомного білка L10, який розміщується в лідерній послідовності, що передує генам rplJL. Консервативність структурової організації сайта у двох видів Streptomyces і значна подібність структури до 23S мРНК свідчать про аутогенну регуляцію генів rplJL стрептоміцетів рибосомним білком L10. Описаны структурные особенности обнаруженного у представителей Streptomyces (Streptomyces griseus и Streptomyces coelicolor) потенциального сайта связывания рибосомного белка L10. расположенного в лидерной последовательности, предшествующей генам rplJL. Консервативность структурной организации сайта у двух видов Streptonmyces и высокое подобие структуры с 23S мРНК свидетельствуют об аутогенной регуляции экспрессии генов rplJL стриптомицетов рибосомным белком L10.